Morphological characterisation of Fusarium oxysporum f.sp. lycopersici isolates causing tomato wilt disease in protected houses in Syrian coast - علي صبيح; محمود حسن; قصي الرحية; وفاء شومان (Latakia University Journal -Biological Sciences Series, 2022)
This research aimed to identify the morphological characters of fungus isolates belonging to Fusarium oxysporum f.sp. lycopersici, the causal agent of tomato wilt disease in covered culture in Syrian coast. Seventy tow isolates of the wilt causal agent represented the main protected tomato planting regions in Tartous (Akkar flat, Yahmour, Banias and Alkadmous) and Lattakia (Jableh), and most tomato hybrids (31 hybrids and resistant stocks) were collected. The isolates were regrouped into nine morphotypes based on tow criteria, colony colour on the upper and down face of the colony, and mycelium texture (densely floccose, floccose, flocculose). The nine morophotypes were compared according to sporulation density, daily colony growth rate and spore dimensions, significant differences among them were recorded. The correlation between conidiospore long and width was strong and positive, and negative among other studied criteria.